QOLP-23. PALLIATIVE CARE AND END OF LIFE HEALTHCARE UTILIZATION IN PATIENTS WITH INCURABLE PRIMARY MALIGNANT BRAIN TUMORS. (5th November 2018) - Bhatt, Sunil; El-Jawahri, Areej; Nipp, Ryan; Batchelor, Tracy; Temel, Jennifer; Forst, Deborah
Abstract: BACKGROUND: Patients with primary malignant brain tumors (PMBT) experience high symptom burden and mortality. However, their healthcare utilization at the end of life, including palliative care utilization, has not been well studied. METHODS: We conducted a single-center, retrospective analysis of deceased patients diagnosed with PMBT between 1/1/12 and 8/31/15. We assessed healthcare utilization including hospitalizations, palliative care usage and hospice enrollment. RESULTS: We identified 200 patients with incurable PMBT within the above timeframe. The majority of patients (86.0%, 171/200) had a diagnosis of glioblastoma. Most patients were white (185/200, 93.0%), non-Hispanic (189/200, 95.5%), and male (117/200, 59.0%). Median survival was 13.8 months. When excluding hospitalizations for planned procedures or chemotherapy, the median number of hospitalizations was 2 (range 0–9). In the last 30 days of life, 61/200 patients (30.5%) were hospitalized. Notably, only 63/200 (31.5%) patients ever received a palliative care consultation. The majority of these patients (39/63, 61.9%) were seen by palliative care only as inpatients. Of those seen by palliative care, only 19/63 (30.2%) had their first contact in the outpatient setting. The median time from first palliative care consultation to death was 53 days (range 0–981) and from first inpatient consultation to death was 32 days (range 0–354). Most patients were enrolled in hospice prior to death (154/200, 77.0%), with a median length of stay in hospice of 25 days (range 0–405). The majority of patients (112/200, 56.0%) died at home, 6.5% (13/200) died in the hospital, while 29.5% (59/200) died in a skilled nursing or hospice facility. CONCLUSIONS: Despite the known poor prognosis in patients with PMBT, palliative care is used infrequently, late in the disease course and typically initiated only in the inpatient setting. As such, there is a need to develop and study interventions to ensure timely outpatient palliative care referral in this population.